Physiological Responses of Kosteletzkya virginica to Coastal Wetland Soil - Hongyan Wang; Xiaoli Tang; Honglei Wang; Hongbo Shao (The Scientific World Journal, 2015)
Effects of salinity on growth and physiological indices of Kosteletzkya virginica seedlings were studied. Plant height, fresh weight (FW), dry weight (DW), and net photosynthetic rate (Pn) increased at 100 mM NaCl and slightly declined at 200 mM, but higher salinity induced a significant reduction. Chlorophyll content, stomatal conductance (Gs), intercellular CO2 concentration (Ci), and transpiration rate (E) were not affected under moderate salinities, while markedly decreased at severe salinities except for the increased Ci at 400 mM NaCl. Furthermore, no significant differences of Fv/Fm and ΦPSII were found at lower than 200 mM NaCl, whereas higher salinity caused the declines of Fv/Fm, ΦPSII, and qP similar to Pn, accompanied with higher NPQ. Besides, salt stress reduced the leaf RWC, but caused the accumulation of proline to alleviate osmotic pressure. The increased activities of antioxidant enzymes maintained the normal levels of MDA and relative membrane permeability. To sum up, Kosteletzkya virginica seedlings have good salt tolerance and this may be partly attributed to its osmotic regulation and antioxidant capacity which help to maintain water balance and normal ROS level to ensure the efficient photosynthesis. These results provided important implications for Kosteletzkya virginica acting as a promising multiuse species for reclaiming coastal soil.